Web ontology of the music scores of Jose Maceda compositions using Arc2 framework - Pascua, Sonia M.
The main objective of this study is to provide a web ontology for the music scores of the Jose Maceda Compositions by extending not only the Music Ontology (MO) but also some of the many available extensions to MO. MO is an online community effort that provides a model for publishing structured music-related data and uses a variety of RDF and compatible documents and formats to express data on the Semantic Web. It has a unique approach of starting the data description from basic topics and building them into a larger framework instead of covering all topics within the music domain. This allows other ontologies to be plugged on top of the MO namespaces and referenced as Music Ontology Modules, which is used to extend the ontology. Music Scores Web Ontology (MSWO), as this research's metadata description is called, enables representation of data in "triples" thru the use of Resource Description Framewokk (RDF), Simple Protocol and RDF Query Language (SPARQL) for databasing and Arc2 Framework, a PHP semantic tool. It also becomes extensible to define its own format, data types and routines for the module of the Music Scores. Additionally MSWO discusses how it is used in the exploration and comparative evaluation of the metadata schemata across digital repositories and collections by enriching search results from the web data. Adoption of the methodology to the entire collection of the Jose Maceda Collection (JMC) is recommended as future work.